Eclipse mapping of EXO 0748–676: evidence for a massive neutron star. Issue 4 (23rd December 2021) - Knight, Amy H; Ingram, Adam; Middleton, Matthew; Drake, Jeremy
ABSTRACT: Determining the maximum possible neutron star (NS) mass places limits on the equation of state (EoS) of ultra-dense matter. The mass of NSs in low-mass X-ray binaries can be determined from the binary mass function, providing independent constraints are placed on both the binary inclination and mass ratio. In eclipsing systems, they relate via the totality duration. EXO 0748–676 is an eclipsing NS low-mass X-ray binary with a binary mass function estimated using stellar emission lines from the irradiated face of the companion. The NS mass is thus known as a function of mass ratio. Here, we model the X-ray eclipses in several energy bands, utilizing archival XMM–Newton data. We find a narrow region of absorbing material surrounding the companion star is required to explain the energy-dependent eclipses. Therefore, we suggest the companion may be experiencing ablation of its outer layers and that the system could transition into a redback millisecond pulsar. Our fit returns a mass ratio of q=0.222^+0.07_-0.08 and an inclination i = 76.5 ± ^1.4_1.1 . Combining these with the previously measured radial velocity of 410 ± 5 km s −1, derived from Doppler mapping analysis of H α emission during quiescence, returns an NS mass of ∼2 M⊙ even if the line originates as far from the NS as physically possible, favouring hard EoS. The inferred mass increases for a more realistic emission point. However, a ∼1.4 M⊙ canonical NS mass is possible when considering radial velocity values derived from other emission lines observed both during outburst and quiescence.